Characterization and mechanical properties of kenaf cellulose nanocrystal reinforced nanohybrid dental composite from agricultural biowaste - Sheng, Su Bing (2023)
The innovation of nanocellulose as reinforcement filler in composites has attracted interest in various fields for development of new biomaterials. This study aims to characterize cellulose nanocrystals (CNC) extracted from kenaf as reinforcement filler in rice husk silica nanohybrid dental composite. The kenaf fiber reinforced composite was evaluated in terms of flexural and compressive strength. Features of fractured flexural samples were also investigated. Kenaf CNC was isolated from a series of chemical processes, then treated with γ-methacryloxypropyltrimethoxysilane (γ- MPS). Properties of CNC was characterized using transmission electron microscope (TEM), Fourier transform infrared spectroscopy (FTIR) and thermogravimetric analysis (TGA). Experimental composite was fabricated with different fiber loading of 1wt%, 2wt%, 3wt%, 4wt%, 6wt% silane-treated kenaf CNC, which are K0, K1, K2, K3, K4, K6 respectively. Commercial composite of Filtek Z350XT(3M ESPE, USA), Neofil (Kerr Corporation, USA), and Ever-X Posterior (GC Corporation, Tokyo, Japan) were used as comparison. Seven composite specimens were prepared for each group (n=7) using stainless steel molds with dimensions 25mm x 2mm x 2mm bars and 6mm x 4mm cylinders for evaluation of flexural and compressive strength respectively. After light curing using a light cure unit (Elipar Deep Cure L, 3M, USA) for 40 seconds, specimens were tested using an Instron Universal Testing Machine (Shimadzu, Japan). SEM was used to examine fractured flexural samples. Average diameter of kenaf CNC under TEM was 6.31nm. FTIR results suggested adsorption of γ-MPS on kenaf CNC. TGA results did not show significant improvement in thermal properties. For flexural and compressive strength tests, one-way ANOVA showed statistically significant difference (P<0.05) between all groups. The incorporation of kenaf CNC (1wt%) into rice husk silica nanohybrid dental composite has shown slight improvement in mechanical properties. SEM analysis showed fibers as crack stoppers despite suboptimum interfacial adhesion. The results indicate that 1 wt% of kenaf CNC is optimum for reinforcement of rice husk silica nanohybrid dental composite. Excessive fiber content can result in decline in mechanical properties due to poor dispersion of fibers within composite. Kenaf CNC is a viable reinforcement co-filler at low concentrations and may be further studied to fully elicit its profound properties.